If f(x) = (x^2 - x)/(x - 1) and g(x) = x, s it true that f = g?

Expert Answers

An illustration of the letter 'A' in a speech bubbles

The function `f(x) = (x^2 - x)/(x - 1)` and g(x) = x.

It is possible to write f(x) as:

`f(x) = (x^2 - x)/(x - 1)`

= `(x*(x - 1))/(x - 1)`

Now the common factor x - 1 can be...

(The entire section contains 118 words.)

Unlock This Answer Now

Start your 48-hour free trial to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Start your 48-Hour Free Trial
Approved by eNotes Editorial Team